STRATEGI BADAN USAHA MILIK DESA (BUMDes) DALAM PENINGKATAN PENDAPATAN ASLI DESA DI DESA TIBUBENENG KECAMATAN KUTA UTARA KABUPATEN BADUNG - Febryanti Putri, Ayu Devi; Yudharta, I Putu Dharmanu; Prabawati, Putu Anik (CITIZEN CHARTER, 2021)
Village-owned Enterprises (BUMDes) Gentha Persada that located in Tibubeneng Village, North Kuta District, Badung Regency ranked first as the best BUMDes in Badung Regency. However, BUMDes Gentha Persada still has problems such as not being able to achieve its target, which is to contribute in increasing the village's original income optimally.The results of this study indicate that the BUMDes Gentha Persada has carried out a strategic management process and there are several obstacles in increasing the village's original income such as lack of regulation from the village government in running the BUMDes program, lack of awareness of human resources in carrying out their duties, and lack of socialization carried out by BUMDes Gentha Persada. The results of the SWOT Matrix analysis resulted in four alternative strategies which became alternative strategies of strengths-opportunity, weakness-opportunity, strengths-threats, and weakness-threats. Keywords:Village-owned Enterprises, Strategic Management Process, SWOT Analysis, Increasing Village Original Income.